Study on occupational ventilatory defects among workers employed in cement factories of Darjeeling district, West Bengal, India - Payel Sarkar; Daliya Biswas; Eashin Gazi; Kaushik Ishore (Wolters Kluwer Medknow Publications, 2022)
Introduction: Cement factory workers are at a high risk of exposure to crystalline silica-laden cement dusts and at a higher risk of developing chronic obstructive pulmonary disease (COPD), like chronic bronchitis, emphysema and restrictive lung disease like silicosis. This study was done to measure the extent of occupational ventilatory defect among workers employed inside cement factories. Material and Methods: A cross sectional study was conducted among cement factory workers using questionnaire on respiratory symptoms 1986 and spirometry was done after seeking permission from the concerned authority and Institutional Ethics Committee. Logistic regression analysis was done to test for statistical significance. Results: Ventilatory defect was present among one fourth of the factory workers. Obstructive type of lung disease was much higher (94.6%) than restrictive lung disease (5.4%). Almost half of the study subjects had presented with different types of respiratory symptoms. Breathlessness on exertion was commonest symptom, followed by cough day and night. Ventilatory defects were noted to be much higher (86.5%) among the workers working in the cement factories for more than 10 years and increasing trend was observed with increment in their age and years of working at the factory. Ventilatory defect were significantly high among smokers (29.5%), subjects who started smoking in early age (35.9%) and there is increasing trend of defects with a greater number of cigarettes intake. Conclusion: Periodically awareness generation and mandatory use of personal protective equipment should be practiced among workers in cement factories.